2017
DOI: 10.3390/molecules22060913
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel 2-Pyrrolidone-Fused (2-Oxoindolin-3-ylidene)methylpyrrole Derivatives as Potential Multi-Target Tyrosine Kinase Receptor Inhibitors

Abstract: Signaling pathways of VEGFs and PDGFs are crucial in tumor angiogenesis, which is essential in solid tumor progression and metastasis. This study reports our strategy for designing and synthesizing a series of novel 2-pyrrolidone-fused (2-oxoindolin-3-ylidene)methylpyrrole derivatives as potential multi-target tyrosine kinase receptor inhibitors. The target compounds were obtained by condensation of 5-substituted oxindoles with N-substituted 2-pyrrolidone aldehyde 7 in satisfactory yields. Of these, 11 and 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Given the high inhibitory potency of anlotinib toward VEGFR2 in enzymatic assays, we carried out a molecular docking approach to investigate the potential binding sites of anlotinib in VEGFR2 and its possible binding mode. According to previous reports, the ATP‐binding pocket of VEGFR2 is defined as including a hinge region and a hydrophobic region . As shown Figure B, residues of the hinge region (Cys919 and Glu917) can form hydrogen bonds with adenine mimics.…”
Section: Resultsmentioning
confidence: 99%
“…Given the high inhibitory potency of anlotinib toward VEGFR2 in enzymatic assays, we carried out a molecular docking approach to investigate the potential binding sites of anlotinib in VEGFR2 and its possible binding mode. According to previous reports, the ATP‐binding pocket of VEGFR2 is defined as including a hinge region and a hydrophobic region . As shown Figure B, residues of the hinge region (Cys919 and Glu917) can form hydrogen bonds with adenine mimics.…”
Section: Resultsmentioning
confidence: 99%
“…Lee and co-workers developed a novel class of multitarget inhibitors of VEGFR and PDGFR through condensation of 2-pyrrolidone aldehyde with oxindoles. 174 Two compounds (69, and 70) exhibited potent antiproliferative and enzymatic activities compared with sunitinib. They could be used as novel angiogenesis inhibitors in the treatment of cancers.…”
Section: Multitarget Rtkis As Antiangiogenic Agentsmentioning
confidence: 99%
“…It is under clinical assessment for the treatment of cancers. Lee and co‐workers developed a novel class of multitarget inhibitors of VEGFR and PDGFR through condensation of 2‐pyrrolidone aldehyde with oxindoles . Two compounds ( 69 , and 70 ) exhibited potent antiproliferative and enzymatic activities compared with sunitinib.…”
Section: Recent Advances In Small‐molecule Antiangiogenic Agentsmentioning
confidence: 99%
“…Given the effectiveness of famitinib, our previous study successfully synthesized a series of novel five-membered-heterocycle derivatives of 2-pyrrolidone fused (2-oxoindolin-3-ylidene)methylpyrrole I (Fig. 1 ) [ 19 ]. In contrast to famitinib, our synthetic compounds possess a more rigid conformation than sunitinib and demonstrated superior inhibitory activity of VEGFR-2 and PDGFRβ to sunitinib.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to famitinib, our synthetic compounds possess a more rigid conformation than sunitinib and demonstrated superior inhibitory activity of VEGFR-2 and PDGFRβ to sunitinib. Among them, C(5)-Br 2-pyrrolidone-fused (2-oxoindolin-3-ylidene)methylpyrrole showed that potency against VEGFR-2 was fivefold higher in comparison to sunitinib [ 19 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%